Profile Of Reading Comprehension Ability In Students: Profil Kemampuan Membaca Pemahaman Pada Siswa - Sari, Anggraeni Swastika; Kusumaningtyas, Nuraini (Procedia of Social Sciences and Humanities, 2024)
One of the important skills for a student is reading. Reading is a window to the world, where by reading students will be able to understand and analyze information and expand their knowledge horizons. This research aims to see a picture of reading comprehension abilities in undergraduate students. The approach taken is quantitative descriptive. The method used is a test, namely reading speed and reading comprehension. The research population was undergraduate psychology students with a sample size of 138. The sampling technique was random sampling using the NIM of undergraduate students. The data analysis technique is descriptive statistics using Jamovi. Based on data analysis, the results showed that in general the reading speed of undergraduate students tended to be slow with an average speed of 131 Kpm as much as 75.4%. The level of understanding of reading content is in the low category, namely with an average PI% value of 45.7 as much as 92%. In general, it can be said that the reading comprehension ability of undergraduate students still tends to be low with an average of 77.8 Kpm with a reading comprehension of 49.1%. This means that undergraduate students' reading comprehension is less than 70% of 350 Kpm. For other researchers who are interested in the same theme, they can find effective interventions to improve undergraduate students' reading comprehension abilities.